Ontogeny of the B- and T-cell response in a primary Zika virus infection of a dengue-naïve individual during the 2016 outbreak in Miami, FL. - Michael J Ricciardi; Diogo M Magnani; Alba Grifoni; Young-Chan Kwon; Martin J Gutman; Nathan D Grubaugh; Karthik Gangavarapu; Mark Sharkey; Cassia G T Silveira; Varian K Bailey; Núria Pedreño-Lopez; Lucas Gonzalez-Nieto; et al. (Public Library of Science (PLoS), 2017)
Zika virus (ZIKV) is a mosquito-borne flavivirus of significant public health concern. In the summer of 2016, ZIKV was first detected in the contiguous United States. Here we present one of the first cases of a locally acquired ZIKV infection in a dengue-naïve individual. We collected blood from a female with a maculopapular rash at day (D) 5 and D7 post onset of symptoms (POS) and we continued weekly blood draws out to D148 POS. To establish the ontogeny of the immune response against ZIKV, lymphocytes and plasma were analyzed in a longitudinal fashion. The plasmablast response peaked at D7 POS (19.6% of CD19+ B-cells) and was undetectable by D15 POS. ZIKV-specific IgM was present at D5 POS, peaked between D15 and D21 POS, and subsequently decreased. The ZIKV-specific IgG response, however, was not detected until D15 POS and continued to increase after that. Interestingly, even though the patient had never been infected with dengue virus (DENV), cross-reactive IgM and IgG binding against each of the four DENV serotypes could be detected. The highest plasma neutralization activity against ZIKV peaked between D15 and D21 POS, and even though DENV binding antibodies were present in the plasma of the patient, there was neither neutralization nor antibody dependent enhancement (ADE) of DENV. Interestingly, ADE against ZIKV arose at D48 POS and continued until the end of the study. CD4+ and CD8+ T-cells recognized ZIKV-NS2A and ZIKV-E, respectively. The tetramer positive CD8+ T-cell response peaked at D21 POS with elevated levels persisting for months. In summary, this is the first study to establish the timing of the ontogeny of the immune response against ZIKV.